Implementasi Algoritma A-Star Untuk Pencarian RuteTerdekat Titik Shelter Evakuasi Tsunami - Renita Astri; Sularno (Ikatan Ahli Informatika Indonesia (IAII), 2020)
District of West Padang which is the area closest to the coast and has a high population. Therefore a geographic information system was created using the A-Star Algorithm method. The A-Star algorithm uses the closest distance estimation to reach a goal and has a heuristic value that is used as a basis for consideration. In this system there are alternative paths and show the amount of capacity and distance from the shelter to be addressed.